2011
DOI: 10.1080/19393210.2011.561931
|View full text |Cite
|
Sign up to set email alerts
|

Intake of aflatoxins through the consumption of peanut products in Brazil

Abstract: To estimate daily intake of aflatoxins from peanut products consumed by the population of Paraná State (Brazil), 100 samples of peanut products were collected between July 2006 and April 2007. Aflatoxins were determined by an HPLC method with fluorescence detection. There was a 50% occurrence of aflatoxins (B1, B2, G1 and G2) in concentrations ranging from 0.5 to 113 ng g(-1), with 13 samples with levels above 20 ng g(-1). Intake was calculated for average and high adult consumers of peanut products and it was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…No sample had AFB 1 or AFM 1 above the tolerance limits established by Brazilian regulations for peanut, corn or dairy products (Agência Nacional De Vigilância Sanitária, 2011). Peanuts products showed the highest values for AFB 1 contamination when compared with the other samples analyzed, which is in agreement with previous reports on the incidence of aflatoxins in those products (Jager et al, 2014;Magrine et al, 2011). Corn flour had the lowest AFB 1 mean concentration among corn products, but with the highest incidence of positive samples (>60%).…”
Section: Methods Performancesupporting
confidence: 93%
See 3 more Smart Citations
“…No sample had AFB 1 or AFM 1 above the tolerance limits established by Brazilian regulations for peanut, corn or dairy products (Agência Nacional De Vigilância Sanitária, 2011). Peanuts products showed the highest values for AFB 1 contamination when compared with the other samples analyzed, which is in agreement with previous reports on the incidence of aflatoxins in those products (Jager et al, 2014;Magrine et al, 2011). Corn flour had the lowest AFB 1 mean concentration among corn products, but with the highest incidence of positive samples (>60%).…”
Section: Methods Performancesupporting
confidence: 93%
“…Mean PDI varied among different sampling times, ranging from 0.09 ± 0.09 to 1.35 ± 5.98 ng/kg b.w./day, which are similar to data reported previously in the States of Paraná (Magrine et al, 2011) and São Paulo (Jager et al, 2013). There is no consensus for tolerable daily intake of AFB 1 or AFM 1 .…”
Section: Analyses Of Aflatoxin B 1 Metabolites In Serum and Urinesupporting
confidence: 74%
See 2 more Smart Citations
“…In the present study, HCC, VC, and AC liver specimens from patients autopsied in São Paulo showed detectable levels of AFB 1 residues. Previous studies demonstrated that, in general, levels of aflatoxin reported in foodstuffs commercialized in Brazil [ 25 , 26 ] complied with the limits determined by local regulations [ 4 ]. Studies on biomarkers of AFB 1 exposure in urine [ 27 , 28 ] and serum [ 29 ] in individuals from the state of São Paulo corroborate these findings, as they indicated low exposure to the toxin in foodstuffs.…”
Section: Discussionmentioning
confidence: 92%